(untitled) (Iter, 2022)
W uith admiration Gabriela Mistral praises and evalúes the art, literature and religión of Medieval and Renaissance Italy; centering it in Florence. She points out its aesthehtic, ethic and religious traits, which have Consolidated herown poetic creed.